Devil's bargain: Steve Bannon, Donald Trump, and the storming of the presidency - Green, Joshua (Penguin Press, 2017)
The elevation of Bannon to head Trump's flagging presidential campaign on August 17, 2016, seemed to signal the meltdown of the Republican Party. Bannon was a bomb-throwing pugilist despised by Democrats and Republicans alike. Green shows that, to understand Trump's extraordinary rise and Clinton's fall, you have to weave Trump's story together with Bannon's, or else it doesn't make sense